PERBANDINGAN METODE INTERPOLASI GEOSTATISTIK UNTUK HUTAN ALAM - Arseno Satrio Utomo; Syam’ani Syam’ani; Rina Kanti (Jurnal Sylva Scienteae, 2020)
Specially Designed Forest Area (KHDTK) is a forest area designated for research and development, education and training purposes as well as local religious and cultural interests. The purpose of this research is to analyze the potential of Natural Forest in KHDTK Mandiangin Forest Area using geostatistical interpolation method and Testing the most accurate geostatistical interpolation method for mapping the forest potency, especially the Mandiangin hill forest in KHDTK area. The research data were taken by plot size determination technique, stratification stratification with SPOT-5 image, Stratified Random Sampling, Field Survey (observation), Potential Analysis of Mandiangin Forest Standing. The expected benefit of this research is to obtain the accurate description data of a number of geostatistical interpolation methods so that it can be a consideration of the value of related value in performing inventory of stand potential especially for stand case in natural forest of hill Mandiangin in area (KHDTK). Based on this research, Ordinary Krigging and Universal Krigging interpolation methods produce the smallest or most accurate RMSE in comparison with the IDW and Simple Krigging interpolation methods.Keywords ;Interpolation, Geostatistics, Natural Forest